MEF2A regulates mGluR-dependent AMPA receptor trafficking independently of Arc/Arg3.1 - Carmichael, Ruth E. (Sci Rep, 2018)
Differential trafficking of AMPA receptors (AMPARs) to and from the postsynaptic membrane is a key determinant of the strength of excitatory neurotransmission, and is thought to underlie learning and memory. The transcription factor MEF2 is a negative regulator of memory in vivo, in part by regulating trafficking of the AMPAR subunit GluA2, but the molecular mechanisms behind this have not been established. Here we show, via knockdown of endogenous MEF2A in primary neuronal culture, that MEF2A is specifically required for Group I metabotropic glutamate receptor (mGluR)-mediated GluA2 internalisation, but does not regulate AMPAR expression or trafficking under basal conditions. Furthermore, this process occurs independently of changes in expression of Arc/Arg3.1, a previously characterised MEF2 transcriptional target and mediator of mGluR-dependent long-term depression. These data demonstrate a novel MEF2A-dependent mechanism for the regulation of activity-dependent AMPAR trafficking.